2023
DOI: 10.1097/qad.0000000000003617
|View full text |Cite
|
Sign up to set email alerts
|

PrEP initiation, persistence, and adherence during pregnancy through the postpartum period: a prospective analysis in Kenya

Jillian Pintye,
John Kinuthia,
Felix Abuna
et al.

Abstract: Objective: We evaluated pre-exposure prophylaxis (PrEP) initiation, persistence, and adherence measured via tenofovir-diphosphate (TFV-DP) concentrations in dried blood spots (DBS) among women offered PrEP during pregnancy. Methods:We prospectively analyzed data from participants in the PrIMA Study (NCT03070600) who were offered PrEP during the second trimester and followed through 9 months postpartum. At follow-up visits (monthly in pregnancy; 6 weeks, 6 months, 9 months postpartum), self-reported PrEP use wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Adherence was higher in pregnancy compared to postpartum and having a partner with a known HIV infection was the most significant predictor of initiation, adherence, and continued use. Interestingly tolerance to ARVs side effects was not an important predictor of adherence ( 9 ). The PrIYA program in Kenya evaluated pregnancy outcomes in 1530 mother-child pairs in Kenya, including 206 women who initiated TDF/FTC pre-conception compared to 1,324 with no TDF/FTC exposure ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence was higher in pregnancy compared to postpartum and having a partner with a known HIV infection was the most significant predictor of initiation, adherence, and continued use. Interestingly tolerance to ARVs side effects was not an important predictor of adherence ( 9 ). The PrIYA program in Kenya evaluated pregnancy outcomes in 1530 mother-child pairs in Kenya, including 206 women who initiated TDF/FTC pre-conception compared to 1,324 with no TDF/FTC exposure ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of new HIV infections in pregnant and breastfeeding women, as well as adolescent girls and young women (15-24 years), has declined (although at a slower rate compared to adolescent male counterparts) with Graybill et al, reporting HIV incidence of 4.1 per 100 person years (95% PI: 1.1, 12.2) pre-2010, compared to 2.1/100 person years (95% PI: 0.7, 6.5) post-2014 (4,6,7). Several studies have clearly demonstrated the efficacy and acceptability of pre-exposure prophylaxis for HIV (PrEP) in pregnant as well as non-pregnant and breastfeeding women (8)(9)(10)(11)(12)(13)(14)(15). National HIV programmes globally are implementing policies that include the rollout of products for the prevention of HIV in all populations considered to be at risk, including WOCP, pregnant and breastfeeding women (16-18).…”
Section: Introductionmentioning
confidence: 99%